Cement grinding aid as well as preparation method and application thereof

By using fly ash carrier and polyol amines, polyols, polyphenyl alcohol ethers and other components in cement aids, a water insulation film is formed, which solves the problems of ball paste grinding, yield reduction and strength reduction of high-water content raw materials during ball grinding, and achieves the effect of improving the fluidity and strengthening of cement powder.

CN119591347AActive Publication Date: 2025-03-11HUAXIN CEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411788259.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Existing cement aids are difficult to effectively disperse moisture in high moisture content raw materials, resulting in problems such as grinding of paste ball paste, lowering yield and decreasing cement strength.

Method used

Fly ash is used as a carrier, combining polyolamines, polyols, polyphenylene alcohol ethers, hydrophobic silica, silane polyethylene glycol and other components, and through surface modification and the synergistic effect of components, a water insulation film is formed to improve the water resistance of the cement particles.

Benefits of technology

It effectively improves the fluidity of cement powder in the grinding process, reduces the adverse impact of moisture on the grinding process, solves the problems of ball paste grinding, lower yield and lower strength of high-water content raw materials during the ball grinding process, and promotes cement hydration and improves cement strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174662260000091
    Figure BDA0005174662260000091
  • Figure BDA0005174662260000101
    Figure BDA0005174662260000101
  • Figure BDA0005174662260000111
    Figure BDA0005174662260000111
Patent Text Reader

Abstract

The invention discloses a cement grinding aid which comprises the following components in parts by mass: 300-500 parts of fly ash, 15-40 parts of an organic grinding aid component, 2-8 parts of an inorganic grinding aid component, 1-3 parts of a dehydrating agent, 3-6 parts of a water absorbent, 2-5 parts of hydrophobic silicon dioxide and 8-13 parts of double-end silane polyethylene glycol, through component matching optimization and surface modification, the capacity of cement particle surfaces for resisting moisture in a mixed material is improved, meanwhile, absorption and volatilization of the moisture in the mixed material are effectively accelerated, and the fluidity of cement powder in a mill is effectively improved; the problems that an existing grinding aid cannot solve the problems that a high-moisture-content raw material is burnt in the ball-milling process, the yield is reduced, and the strength is reduced in the application process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a cement grinding aid and a preparation method and application thereof. Background Art

[0002] At present, cement concrete has become one of the most widely used and widely used engineering structural materials, and cement concrete has become an important material basis for the development of human society. The cement industry is not only a major consumer of resources and energy and a major carbon emitter, but also has huge space and potential for energy conservation and emission reduction. It is a key area for my country to achieve energy conservation and emission reduction and achieve low-carbon development. The use of industrial waste slag as a mixed material to produce cement has achieved good application results, significantly reducing resource and energy consumption and carbon dioxide emissions in the cement production process, reducing cement production costs, and eliminating environmental pollution caused by industrial waste slag, which has been actively promoted by cement companies.

[0003] With the continuous improvement of the application technology of industrial waste slag in cement, the types of industrial waste slag are increasing, and the amount of industrial waste slag added is increasing. The production process of industrial waste slag determines that its composition will contain a large amount of water (more than 20% or even higher), such as slag produced by water quenching of the residue produced in the process of smelting pig iron, lithium slag produced by the process of producing lithium carbonate using sulfuric acid method, desulfurized gypsum obtained by the reaction of flue gas containing SO2 and lime slurry, etc. However, the moisture content of the raw materials entering the mill has a significant impact on the cement ball mill grinding process. When the moisture content is too high, the ball and mill will be sticky. For every 1% increase in the comprehensive moisture content of the raw materials entering the mill, the ball mill output will decrease by 10%; when the comprehensive moisture content of the raw materials entering the mill exceeds 3%, the cement mill output will be significantly reduced, and even serious adhesion will occur in the mill, and production cannot be carried out. Therefore, the moisture content in industrial waste slag limits its application as a cement admixture to a certain extent. In the actual production process, the industrial waste slag is dried to reduce the moisture content, but this method is not only energy-intensive but also inefficient.

[0004] Cement grinding aids have been widely used by cement companies as an additive to improve grinding efficiency and grinding conditions. However, at present, grinding aids mainly achieve the dispersion of cement particles by shielding the charges generated by bond breaking during the grinding process of cement particles and eliminating static electricity. When the moisture content of cement raw materials is high, electrostatic adsorption is less, and existing grinding aids are difficult to play an effective role. The main grinding aid components of existing grinding aids are polyol amines and polyol substances. There are a large number of hydroxyl groups in the molecules. After being adsorbed on the surface of cement particles, the hydroxyl groups will further absorb moisture in the raw materials, which will aggravate the adverse effect of moisture on cement grinding. In addition, the polyol amine component in the existing grinding aids will promote cement hydration, causing cement to prehydrate after absorbing water and reduce cement strength. Therefore, the existing grinding aids cannot solve the problems of ball grinding and reduced output of raw materials with high moisture content during ball milling, as well as reduced strength during application.

[0005] CN 104045257 A discloses a high-moisture mixed material cement grinding aid, the raw material composition is: 40-55% of polyol grinding aid mother liquor, 0.01-0.5% of acrylic acid, 1-10% of ammonium sulfate, 0.02-0.05% of sodium dodecylbenzene sulfonate, 2-5% of triethanolamine, 1-5% of sugarcane sugar residue liquid, and the balance is water, the total amount is 100%; the percentages are all mass percentages. The preparation method of the polyol grinding aid mother liquor is as follows: in a reaction pot, 2 parts of maleic anhydride and 1 part of polyol are added and mixed evenly, and the mixture is reacted at 100° C. for 3 hours to synthesize the polyol grinding aid mother liquor. The patent modifies the polyol by acid and combines with sodium dodecylbenzene sulfonate to improve the fluidity of cement powder, but the raw materials used are all substances with hydrophilic groups, which cannot effectively isolate water from cement particles and have limited effect.

[0006] CN 116023060 A discloses a cement grinding aid that resists moisture absorption and caking, wherein the main grinding aid components include N-□tert-butyloxycarbonyldiethanolamine, an alcohol amine compound and a glycol compound, and the solvent is water. The patent uses one end of N-□tert-butyloxycarbonyldiethanolamine to adsorb on the surface of cement particles, and uses the ester group and polymethyl hydrophobicity of the other end to isolate moisture, thereby improving the cement's ability to resist moisture absorption and caking. However, the ester group in the structure of N-tert-butyloxycarbonyldiethanolamine is unstable, and the substance itself has limited hydrophobicity, so the effect of improving the grinding process of high-moisture mixed cement is limited.

[0007] CN 116986844 A discloses a grinding aid for improving cement hygroscopicity, wherein the components thereof are as follows by mass percentage: 6% to 15% of a polyol mono-fatty acid ester compound, 12% to 48% of a polyol amine mono-fatty acid ester compound, 1% to 6% of a gypsum dehydration inhibitor, 3% to 7% of a grinding aid film-forming agent, 0.5% to 3.0% of a titanate coupling agent, 0.1% to 0.5% of a defoaming agent, and the remainder is water. The invention utilizes the ester group of the side chain of the polyol mono-fatty acid ester compound and the polyol amine mono-fatty acid ester compound and the hydrophobicity of the alkyl long chain to improve cement hygroscopicity, but the ester group is easily decomposed during the grinding process of cement with high water content, and the effect is limited.

[0008] CN 114634322 A provides a cement strength anti-decay agent and its preparation method and application, the raw materials are: polyacid 10%-15%, polyphosphate 5%-10%, SAP super absorbent resin 0.1%-0.5%, sulfonate 3%-8%, alcohol amine substance 5%-12%, and the balance is water. The invention utilizes SAP super absorbent resin containing hydrophilic groups and cross-linked structure polymer electrolyte, which has high water absorption function of absorbing water hundreds to thousands times heavier than itself, and has excellent water retention performance. Once it absorbs water and swells to become a hydrogel, it is difficult to separate the water even under pressure. Differential thermal analysis shows that 50% of the water absorbed by the super absorbent resin is still enclosed in the gel network at above 150°C. The addition of the super absorbent resin to cement can effectively absorb the free water in the cement and enclose it in the gel network, thereby avoiding the pre-hydration reaction between the active matter in the cement and the free water, and ensuring that the cement strength will not decay. However, SAP super absorbent resin will absorb water and swell. Its retention in cement will cause instability in the structure of the hydration product and have an adverse effect on the performance of cement.

[0009] The existing technology cannot stably enable cement to resist high moisture in the admixture, nor can it effectively separate cement from moisture. It cannot solve the problems of raw materials with high moisture content causing ball sticking during ball milling, reduced output, and reduced strength during application. Summary of the invention

[0010] The purpose of the present invention is to provide a grinding aid and a preparation method thereof, which can improve the ability of cement particle surfaces to resist moisture in admixtures through component matching optimization and surface modification, effectively accelerate the absorption and volatilization of moisture in admixtures, effectively improve the fluidity of cement powder in the mill, and make up for the problem that existing grinding aids cannot solve the problem of raw materials with high moisture content becoming sticky during ball milling, reducing output, and reducing strength during application.

[0011] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0012] A cement grinding aid comprises the following components by mass: 300-500 parts of fly ash, 15-40 parts of organic grinding aid components, 2-8 parts of inorganic grinding aid components, 1-3 parts of dehydrating agent, 3-6 parts of water absorbent, 2-5 parts of hydrophobic silicon dioxide and 8-13 parts of biterminal silane polyethylene glycol.

[0013] According to the above scheme, the fly ash is Class I fly ash, and the glass microbead content is greater than 60wt%.

[0014] According to the above scheme, the organic grinding aid component is composed of polyol amine, polyol, and polyphenyl alcohol ether; the molar ratio of the polyol amine and the polyol is 1:(0.2-0.5), and the ratio of the sum of the molar amounts of the polyol amine and the polyol to the molar amount of the polyphenyl alcohol ether is 1:1.

[0015] According to the above scheme, the polyol amine is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, triisopropanolamine, N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine or any mixture thereof.

[0016] According to the above scheme, the polyol is one of propylene glycol, 1,2,4-butanetriol, 1,2,3-butanetriol, threitol or any mixture thereof.

[0017] According to the above scheme, the polyphenyl alcohol ether is one of hydroquinone dihydroxyethyl ether and hydroquinone diisopropyl alcohol ether or any mixture thereof.

[0018] According to the above scheme, the inorganic grinding aid component is one of sodium tripolyphosphate and sodium hexametaphosphate or any mixture thereof.

[0019] According to the above scheme, the dehydrating agent is one of isobutyl alcohol, isopropyl alcohol, tert-butyl alcohol or any mixture thereof.

[0020] According to the above scheme, the water absorbent is ((5-carboxyl-1H-pyrazole-3-carbonyl)oxy)(hydroxy)aluminum (III), MOF-303 (AL) metal organic framework, with a specific surface area of ​​800-1200m 2 / g.

[0021] According to the above scheme, the hydrophobic silica is prepared by treating hydrated silica with high hydrogen-containing silicone oil, the treatment method is surface coating, and the particle size range is 5-15 μm.

[0022] According to the above scheme, the molecular weight of the bi-terminal silane polyethylene glycol is 400-2000 g / mol.

[0023] The preparation method of the cement grinding aid comprises the following steps:

[0024] The organic grinding aid component, the inorganic grinding aid component, the dehydrating agent, the water absorbent, the hydrophobic silica and the bi-terminal silane polyethylene glycol are slowly added to the fly ash in sequence, and then the mixture is placed in a mixer and mixed for 60 to 120 minutes to obtain the cement grinding aid.

[0025] The application of the above cement grinding aid in the ball milling process of cement with high moisture content.

[0026] According to the above scheme, the comprehensive moisture content of the raw materials of cement entering the mill is 2-4wt%.

[0027] According to the above scheme, the dosage of the cement grinding aid is 0.3-0.5wt% of the mass of the raw materials entering the mill.

[0028] The present invention uses fly ash as a cement grinding aid carrier, which can effectively carry components of different physical and chemical properties evenly, ensuring the uniformity of the components during the application process. Fly ash containing a large amount of glass microbeads is selected. The lubricating effect of the glass microbeads can increase the powder fluidity of the cement raw materials during the grinding process, increase the flow rate of the material in the mill, and thus help the wind in the mill to take away the moisture and discharge it out of the mill.

[0029] Polyol amines and polyols are good cement grinding aids, but the combination of multiple hydroxyl groups in the structure with water in cement raw materials results in the failure of them to provide good grinding aids in high-moisture cement raw materials. The present invention uses polyphenyl alcohol ethers and polyol amines and polyols with a hydroxyl number greater than 3 to compound, and the hydroxyl groups in the polyphenyl alcohol ether structure can be combined with polyol amines and polyols to be adsorbed on the surface of cement particles together; the benzene ring has good hydrophobicity and rigidity, which can improve the adverse effects of the hydrophilicity of polyol amines and polyols on the one hand, and on the other hand, the rigidity of the benzene ring structure can enhance the grinding aid effect and the stability of the adsorption layer.

[0030] Sodium tripolyphosphate and sodium hexametaphosphate can combine with the broken bonds generated on the surface of cement raw materials during grinding. The same electrical repulsion will prevent the particles from approaching and agglomerating each other, playing a good grinding aid role. In addition, sodium tripolyphosphate and sodium hexametaphosphate can increase the surface energy of the mineral phase of cement raw material particles. Higher surface energy helps hydrophobic silica and silane polyethylene glycol to adsorb on the surface of the mineral phase of cement raw material particles, thereby improving their effect.

[0031] The present invention adopts small molecule alcohol as a dehydrating agent. Small molecule alcohol has a lower surface tension and can improve the ability of other components to be adsorbed on the surface of the mineral phase of cement raw material particles. The grinding temperature of the ball mill is generally 80-120°C. Small molecule alcohol can bond with water to reduce the boiling point of water, thereby accelerating the volatilization of water in the cement raw materials, helping to discharge water out of the mill, and reducing the adverse effects of water on the grinding process.

[0032] MOF-303(Al) is selected as the water-absorbing material. It has good water absorption in low humidity environment and can effectively absorb moisture in cement grinding environment. In addition, MOF-303(Al) can absorb water from cement hydration. 3+ Coordination occurs, accelerating Al 3+ Dissolution promotes cement hydration and improves the strength of cement paste; MOF-303 (Al) has reversible water absorption and exists in cement after grinding. When cement is added with water to form cement paste, the pressure difference formed by the change of water content inside and outside the hydration product can make MOF-303 (Al) release water, and it will not absorb water and swell like SAP super absorbent resin to form an unstable gel structure.

[0033] Hydrophobic silica can isolate moisture from cement particles during cement grinding, thereby improving cement's water resistance. It can undergo hydration reaction in the strong alkaline environment produced by cement hydration, fill in the gaps between hydration products, improve hydration density, and thus improve cement strength.

[0034] Silane polyethylene glycol can significantly improve the wettability of organic grinding aid components and the surface of cement particles. At the same time, the silane structure can bond with hydrophobic silica, improve the adsorption capacity of hydrophobic silica and cement particles, effectively form an adsorption film, and enhance the ability to isolate moisture from contacting cement particles, avoiding the phenomenon of sticky balls and sticky grinding caused by moisture adhering to the surface of cement particles during grinding. Silane-polyethylene glycol-silane with a molecular weight of 400 to 2000 g / mol is selected. If the molecular weight is too small and the polyethylene glycol chain segment is too short, it is not conducive to the formation of the adsorption film; if the molecular weight is too large and the polyethylene glycol chain segment is too long, the hydrophilicity is too strong, which is not conducive to its isolation of moisture from contacting cement particles.

[0035] The present invention uses fly ash as a carrier to effectively and evenly distribute the components therein. The inorganic grinding aid component is used to improve the surface energy of cement particles to enhance the adsorption capacity of other components; under the action of small molecule dehydrating agent to improve surface tension agent dehydrating agent silane polyethylene glycol to improve adsorption capacity, the organic grinding aid component and hydrophobic silica work together to stabilize the surface of cement particles to form a moisture isolation film; the isolated moisture is rapidly discharged under the action of the dehydrating agent and absorbed by the water absorbent at the same time, and the different components work synergistically to effectively improve the phenomenon of ball paste, reduced output and reduced strength of raw materials with high moisture content during ball milling. At the same time, each component not only has no adverse effect on cement hydration, but can promote cement hydration, improve the compactness of cement water products, and effectively improve cement strength.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The raw materials of the cement grinding aid provided by the invention can be obtained through commercial channels, the preparation method is simple, and industrialization can be realized.

[0038] The cement grinding aid provided by the present invention is beneficial to improving the adsorption capacity of organic matter on the surface of cement particles by improving surface energy, surface tension and bridging capacity;

[0039] The cement grinding aid provided by the invention improves the hydrophilicity of existing polyol amines and polyol substances, and enhances the grinding aid effect in the ball milling process of high-moisture cement raw materials.

[0040] The organic grinding aid component, hydrophobic silica and silane polyethylene glycol in the cement grinding aid provided by the present invention work together to stably form a moisture isolation film on the surface of cement particles, effectively improving the ability of cement particles to resist moisture in a high-moisture grinding environment.

[0041] The dehydrating agent in the cement grinding aid provided by the present invention can facilitate the discharge of water in the cement raw materials, and the water absorbing agent can effectively absorb the water in the cement raw materials, thereby effectively reducing the water content of the cement raw materials during the grinding process.

[0042] The different components of the cement grinding aid provided by the invention cooperate with each other to effectively solve the problems of ball sticking, reduced output and reduced strength of raw materials with high moisture content during ball milling.

[0043] The components of the cement grinding aid provided by the present invention not only have no adverse effect on cement hydration, but can promote cement hydration, improve the compactness of cement water products, and effectively improve cement strength. DETAILED DESCRIPTION

[0044] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention. The following specific examples are only some preferred embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, modifications, substitutions and improvements made by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0045] Specific implementation method provides the sources of the test materials, unless otherwise specified, all of which can be obtained through commercial channels.

[0046] Specific implementation method The fly ash used is from Huanggang Dabieshan Power Generation Co., Ltd., meets the requirements of Class I fly ash in national standards, and has a glass bead content of 73%.

[0047] Specific implementation method: Polyphenyl alcohol ether is commercially available, and the manufacturer is Zhongshan Dixin Chemical Co., Ltd.

[0048] Specific implementation method: The water absorbent MOF-303 (Al) is commercially available from Xi'an Qiyue Biotechnology Co., Ltd., with a specific surface area of ​​900m 2 / g.

[0049] Specific implementation method: Hydrophobic silica is obtained from the market, the manufacturer is Anhui Celico Silicon Material Co., Ltd., the model is SH-520, and the particle size range is 5-12 μm.

[0050] Specific implementation method: Silane-polyethylene glycol-silane (double-terminated silane polyethylene glycol) is commercially available from Xi'an Deerta Biotechnology Co., Ltd.

[0051] The organic grinding aid components used in the following Examples 1-10 are weighed according to the molar ratio in Table 1, and polyol amine, polyol, and polyphenyl alcohol ether are mixed uniformly to obtain an organic grinding aid component.

[0052] Table 1

[0053] Example 1 2 3 4 5 6 7 8 9 10 Triethanolamine 1.0 0.1 0.3 0.1 Diethanol monoisopropanolamine 1.0 0.9 0.5 0.4 0.1 0.3 Hydroxyethyl diisopropanolamine 1.0 0.5 0.9 0.3 0.2 0.5 Triisopropanolamine 1.0 0.1 0.7 0.1 Glycerol 0.2 0.2 0.1 0.1 0.5 1,2,4-Butanetriol 0.5 0.1 0.1 0.1 1,2,3-Butanetriol 0.3 0.1 0.2 0.1 0.4 Threitol 0.4 0.1 Hydroquinone dihydroxyethyl ether 1.2 0.7 0.1 1.2 0.7 1.2 1.3 Hydroquinone diisopropyl ether 1.5 0.6 1.3 0.1 0.7 1.5 1.1

[0054] Example 1

[0055] 15 parts of organic grinding aid components, 2 parts of sodium tripolyphosphate, 1 part of isobutanol, 6 parts of MOF-303 (Al), 5 parts of hydrophobic silica, and 8 parts of silane-polyethylene glycol-silane with a molecular weight of 400 g / mol were slowly added to 300 parts of fly ash in sequence, and then placed in a mixer and mixed for 60 minutes to obtain the cement grinding aid.

[0056] Example 2

[0057] 40 parts of organic grinding aid components, 8 parts of sodium hexametaphosphate, 3 parts of isopropanol, 3 parts of MOF-303 (Al), 2 parts of hydrophobic silica, and 13 parts of silane-polyethylene glycol-silane with a molecular weight of 600 g / mol were slowly added to 500 parts of fly ash in sequence, and then placed in a mixer and mixed for 120 minutes to obtain the cement grinding aid.

[0058] Example 3

[0059] To 300 parts of fly ash, 40 parts of organic grinding aid components, 8 parts of sodium tripolyphosphate, 3 parts of tert-butyl alcohol, 3 parts of MOF-303 (Al), 2 parts of hydrophobic silica, and 13 parts of silane-polyethylene glycol-silane with a molecular weight of 800 g / mol were slowly added in sequence, and then placed in a mixer and mixed for 68 minutes to obtain the cement grinding aid.

[0060] Example 4

[0061] 15 parts of organic grinding aid components, 2 parts of sodium hexametaphosphate, 1 part of isobutanol, 6 parts of MOF-303 (Al), 5 parts of hydrophobic silica, and 8 parts of silane-polyethylene glycol-silane with a molecular weight of 1000 g / mol were slowly added to 500 parts of fly ash in sequence, and then placed in a mixer and mixed for 76 minutes to obtain the cement grinding aid.

[0062] Example 5

[0063] To 469 parts of fly ash, 26 parts of organic grinding aid components, 3 parts of sodium hexametaphosphate, 1 part of isobutanol, 1 part of isopropanol, 1 part of tert-butanol, 4 parts of MOF-303 (Al), 3 parts of hydrophobic silica, and 13 parts of silane-polyethylene glycol-silane with a molecular weight of 1200 g / mol were slowly added in sequence, and then placed in a mixer and mixed for 111 minutes to obtain the cement grinding aid.

[0064] Example 6

[0065] 33 parts of organic grinding aid components, 6 parts of sodium hexametaphosphate, 2 parts of isobutanol, 4 parts of MOF-303 (Al), 4 parts of hydrophobic silica, and 10 parts of silane-polyethylene glycol-silane with a molecular weight of 600 g / mol were slowly added to 497 parts of fly ash in sequence, and then placed in a mixer and mixed for 102 minutes to obtain the cement grinding aid.

[0066] Example 7

[0067] 38 parts of organic grinding aid components, 4 parts of sodium tripolyphosphate, 4 parts of sodium hexametaphosphate, 3 parts of isopropanol, 3 parts of MOF-303 (Al), 5 parts of hydrophobic silica, and 10 parts of silane-polyethylene glycol-silane with a molecular weight of 800 g / mol were slowly added to 400 parts of fly ash in sequence, and then placed in a mixer and mixed for 98 minutes to obtain the cement grinding aid.

[0068] Example 8

[0069] 21 parts of organic grinding aid components, 5 parts of sodium tripolyphosphate, 1 part of sodium hexametaphosphate, 1 part of isobutanol, 6 parts of MOF-303 (Al), 3 parts of hydrophobic silica, and 12 parts of silane-polyethylene glycol-silane with a molecular weight of 1000 g / mol were slowly added to 348 parts of fly ash in sequence, and then placed in a mixer and mixed for 82 minutes to obtain the cement grinding aid.

[0070] Example 9

[0071] 17 parts of organic grinding aid components, 2 parts of sodium tripolyphosphate, 4 parts of sodium hexametaphosphate, 1 part of isobutanol, 2 parts of isopropanol, 6 parts of MOF-303 (Al), 5 parts of hydrophobic silica, and 11 parts of silane-polyethylene glycol-silane with a molecular weight of 400 g / mol were slowly added to 425 parts of fly ash in sequence, and then placed in a mixer and mixed for 79 minutes to obtain the cement grinding aid.

[0072] Example 10

[0073] 39 parts of organic grinding aid components, 7 parts of sodium tripolyphosphate, 2 parts of isobutanol, 1 part of tert-butanol, 4 parts of MOF-303 (Al), 4 parts of hydrophobic silica, and 9 parts of silane-polyethylene glycol-silane with a molecular weight of 1200 g / mol were slowly added to 373 parts of fly ash in sequence, and then placed in a mixer and mixed for 91 minutes to obtain the cement grinding aid.

[0074] Comparative Example 1

[0075] Example 1 was repeated, except that hydroquinone dihydroxyethyl ether was not added during the preparation of the organic grinding aid component and other conditions remained unchanged, to obtain a mixture 1.

[0076] Comparative Example 2

[0077] Example 2 was repeated without adding sodium tripolyphosphate and other conditions remained unchanged to obtain mixture 2.

[0078] Comparative Example 3

[0079] Example 3 was repeated without adding isobutanol and other conditions remained unchanged to obtain mixture 3.

[0080] Comparative Example 4

[0081] Example 4 was repeated without adding MOF-303(Al) and keeping other conditions unchanged to obtain mixture 4.

[0082] Comparative Example 5

[0083] Example 5 was repeated without adding silane-polyethylene glycol-silane and keeping other conditions unchanged to obtain mixture 5.

[0084] Comparative Example 6

[0085] Example 6 was repeated, using ethylene glycol in equal amounts to replace propylene glycol, 1,2,3-butanetriol, 1,2,4-butanetriol and threitol, while keeping other conditions unchanged, to obtain mixture 6.

[0086] Comparative Example 7

[0087] Example 7 was repeated, except that an equal amount of acrylic acid-□acrylamide copolymer super absorbent resin SAP was used to replace MOF-303 (Al), and other conditions remained unchanged to obtain mixture 7.

[0088] Comparative Example 8

[0089] Example 8 was repeated, except that an equal amount of silane-polyethylene glycol-silane with a molecular weight of 200 g / mol was used to replace the silane-polyethylene glycol-silane with a molecular weight of 1000 g / mol, and other conditions remained unchanged, to obtain a mixture 8.

[0090] Comparative Example 9

[0091] Example 9 was repeated, except that an equal amount of silane-polyethylene glycol-silane with a molecular weight of 3000 g / mol was used to replace the silane-polyethylene glycol-silane with a molecular weight of 400 g / mol, and other conditions remained unchanged, to obtain a mixture 9.

[0092] The grinding aids for improving cement hygroscopicity prepared in Examples 1 to 10, the mixtures prepared in Comparative Examples 1 to 9, and a commercially available cement grinding aid with triethanolamine and diethylene glycol as main raw materials were tested and evaluated.

[0093] Referring to the test method in GB / T 26748-2011 "Cement Grinding Aids", 5kg of various cement raw materials were added to the test mill according to the PO42.5 cement ratio. The cement ratio was: 80% clinker, 4% slag, 5% lithium slag, 5% coal slag, and 5% desulfurized gypsum. The moisture content of slag was 18.3%, the moisture content of lithium slag was 19.9%, the moisture content of coal slag was 20.5%, and the moisture content of desulfurized gypsum was 19.2%. The comprehensive moisture content of the raw materials entering the mill was 3.9%. Before grinding, the cement grinding aid or mixture was added to the cement raw materials at a dosage of 0.4%. The grinding time was fixed at 25 minutes to obtain the PO 42.5 cement sample out of the mill. After the grinding was completed, the situation in the ball mill was observed and recorded. The repose angle tester was used to test the repose angle of the cement powder out of the mill to characterize the fluidity of the cement powder. The fineness of the cement out of the mill was tested with reference to GB / T 1345-2005 "Test Method for Cement Fineness - Sieve Analysis". The specific surface area of ​​the cement out of the mill was tested with reference to GB / T8074-2008 "Test Method for Specific Surface Area of ​​Cement - Blaine Method". The strength of the cement was tested with reference to GB / T17671-1999 Test Method for Strength of Cement Mortar (ISO Method). The grinding aids prepared in Examples 1 to 10, the mixtures prepared in Comparative Examples 1 to 9, a commercially available cement grinding aid and a blank without cement grinding aid were compared and evaluated, and the results are shown in Tables 2, 3 and 4.

[0094] Table 2

[0095]

[0096]

[0097] From the data in Table 2, it can be seen that the grinding aid prepared by the present invention effectively improves the ball sticking and grinding phenomenon of high-moisture cement raw materials during ball milling, compared with the blank group without grinding aid, the commercially available cement grinding aid and Comparative Examples 1 to 9, and the repose angle of the cement powder out of the mill is smaller and the cement powder fluidity is better. In Comparative Examples 1 to 9, replacing or not adding any component cannot achieve the same effect, which further illustrates the synergistic effect between the components of the grinding aid prepared by the present invention.

[0098] Table 3

[0099] serial number <![CDATA[Specific surface area / m 2 / kg]]> 80μm sieve residue / % 45μm sieve residue / % Blank group 338.6 4.3 18.6 Commercial cement grinding aids 336.9 4.7 19.6 Comparative Example 1 348.6 3.6 16.3 Comparative Example 2 342.1 3.3 15.8 Comparative Example 3 341.2 3.1 17.6 Comparative Example 4 345.6 3.0 15.3 Comparative Example 5 343.2 3.5 17.2 Comparative Example 6 340.1 3.5 16.5 Comparative Example 7 339.9 3.4 16.3 Comparative Example 8 348.7 3.8 15.9 Comparative Example 9 345.6 1.9 16.4 Example 1 363.1 1.6 12.0 Example 2 365.2 1.0 11.3 Example 3 369.6 1.2 10.8 Example 4 359.7 1.2 10.6 Example 5 364.8 1.5 10.5 Example 6 370.3 1.6 11.8 Example 7 361.3 1.1 10.9 Example 8 366.6 1.6 9.6 Example 9 365.2 1.5 11.2 Example 10 367.0 1.4 11.0

[0100] From the data in Table 3, it can be seen that the grinding aid prepared by the present invention significantly increases the specific surface area of ​​cement prepared from high-moisture cement raw materials, reduces the 80μm sieve residue and the 45μm sieve residue, and makes up for the poor grinding effect of commercial cement grinding aids in high-moisture cement raw materials. In Comparative Examples 1 to Comparative Examples 9, replacing or not adding any component cannot achieve the same effect, which further illustrates the synergistic effect between the components of the grinding aid prepared by the present invention.

[0101] Table 4

[0102]

[0103] From the data in Table 4, it can be seen that the grinding aid prepared by the present invention significantly increases the 3d and 28d flexural and compressive strengths of cement compared with the blank group without grinding aid, the commercial cement grinding aid and Comparative Examples 1 to 9, making up for the poor reinforcing effect of the commercial cement grinding aid in high-moisture cement raw materials. In Comparative Examples 1 to 9, replacing or not adding any component cannot achieve the same effect, which further illustrates the synergistic enhancement effect between the components of the grinding aid prepared by the present invention.

Claims

1. A cement grinding aid, characterized in that The composition is as follows by mass: 300-500 parts of fly ash, 15-40 parts of organic grinding aid components, 2-8 parts of inorganic grinding aid components, 1-3 parts of dehydrating agent, 3-6 parts of water absorbent, 2-5 parts of hydrophobic silica, and 8-13 parts of bi-terminal silane polyethylene glycol.

2. The cement grinding aid according to claim 1, characterized in that The fly ash is Class I fly ash, and the glass microbead content is greater than 60wt%.

3. The cement grinding aid as claimed in claim 1, characterized in that The organic grinding aid component consists of polyol amine, polyol and polyphenyl alcohol ether; the molar ratio of the polyol amine to the polyol is 1:(0.2-0.5), and the ratio of the sum of the molar amounts of the polyol amine and the polyol to the molar amount of the polyphenyl alcohol ether is 1:

1.

4. The cement grinding aid as claimed in claim 3, characterized in that The polyol amine is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, triisopropanolamine, and N,N,N,N-tetrakis (2-hydroxyethyl) ethylenediamine, or any mixture thereof; the polyol is one of glycerol, 1,2,4-butanetriol, 1,2,3-butanetriol, and threitol, or any mixture thereof; the polyphenyl alcohol ether is one of hydroquinone dihydroxyethyl ether and hydroquinone diisopropanol ether, or any mixture thereof.

5. The cement grinding aid according to claim 1, characterized in that The inorganic grinding aid component is one of sodium tripolyphosphate and sodium hexametaphosphate or any mixture thereof.

6. The cement grinding aid according to claim 1, characterized in that The dehydrating agent is one of isobutyl alcohol, isopropyl alcohol, tert-butyl alcohol or any mixture thereof; the water absorbing agent is MOF-303 (AL) metal organic framework with a specific surface area of ​​800-1200m 2 / g.

7. The cement grinding aid according to claim 1, characterized in that The hydrophobic silica particle size ranges from 5 to 15 μm; the biterminal silane polyethylene glycol has a molecular weight of 400 to 2000 g / mol.

8. The method for preparing the cement grinding aid according to any one of claims 1 to 7, characterized in that The following steps are involved: The organic grinding aid component, the inorganic grinding aid component, the dehydrating agent, the water absorbent, the hydrophobic silica and the bi-terminal silane polyethylene glycol are slowly added to the fly ash in sequence, and then the mixture is placed in a mixer and mixed for 60 to 120 minutes to obtain the cement grinding aid.

9. The use of the cement grinding aid according to any one of claims 1 to 7 in a high-moisture mixed material cement ball mill grinding process, characterized in that The comprehensive moisture content of the raw materials of cement entering the mill is 2-4wt%.

10. The use of the cement grinding aid as claimed in claim 9 in the process of ball milling of cement with high moisture content admixture, characterized in that The cement grinding aid is added in an amount of 0.3-0.5 wt % of the raw material mass.

Citation Information

Patent Citations

  • High-moisture admixture cement grinding aid and preparation method thereof

    CN104045257A

  • Cement strength anti-attenuation agent as well as preparation method and application thereof

    CN114634322A

  • Liquid cement grinding aid and preparation method thereof

    CN112062493A

  • Cement grinding aid and preparation method thereof

    CN114956649A

  • Grinding aid for cement and preparation method therefor

    WO2023035398A1